Temperature response type aerogel composite thermal fabric and preparation method thereof

By chemically bonding modified silica aerogel with phase change microcapsules, the problems of high brittleness and unstable temperature response of traditional thermal insulation fabrics are solved, achieving long-lasting heat insulation and dynamic temperature control.

CN121407401APending Publication Date: 2026-01-27SHANGHAI LIANGFENG LEADING TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511787340.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-01
Publication Date
2026-01-27

AI Technical Summary

Technical Problem

Traditional thermal insulation fabrics suffer from problems such as high brittleness, easy powdering, inability to dynamically regulate temperature, and unstable bonding between phase change microcapsules and aerogel, resulting in low durability and low temperature response efficiency.

Method used

By chemically bonding modified silica aerogel with phase change microcapsules, and utilizing the flexibility of the long-chain alkyl-modified aerogel skeleton and the active wall material design of the phase change microcapsules, stable amide bond connections are formed. Combined with waterborne polyurethane adhesive to enhance the bonding strength, the chemical bonding of aerogel and microcapsules is achieved.

Benefits of technology

It achieves long-lasting thermal insulation performance and dynamic temperature control capability of the fabric, improves the fabric's durability and temperature response efficiency, and avoids functional layer peeling and thermal insulation performance degradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121407401A_ABST
    Figure CN121407401A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of functional fabrics, in particular to a temperature response type aerogel composite thermal fabric and a preparation method thereof. The warm-keeping fabric comprises a base cloth layer and a warm-keeping functional layer coated on the surface of the base cloth layer, wherein the modified aerogel in the warm-keeping functional layer is modified by long-chain disiloxane and is grafted with amino; the phase change microcapsule takes paraffin as a core material, takes a carboxyl-containing polymer as a wall material and is doped with nano boron nitride. During preparation, amidogen of the modified silicon dioxide aerogel and carboxyl in the phase change microcapsule wall material form amido bonds by combining with a catalyst, the amido bonds and the waterborne polyurethane adhesive are prepared into slurry, the slurry is coated on the base cloth subjected to corona treatment, and the finished product is obtained after drying and curing. The problems that traditional aerogel is embrittled, and microcapsules are prone to falling off are solved, efficient heat insulation and temperature response synergy are achieved, and the fabric is resistant to embrittlement, resistant to washing, high in interlayer bonding and suitable for outdoor, commuting and other scenes with requirements for heat preservation and durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional fabric technology, and in particular to a temperature-responsive aerogel composite thermal insulation fabric and its preparation method. Background Technology

[0002] With the upgrading of consumption and the increasing demand for outdoor and special-purpose clothing, the market requirements for thermal insulation fabrics have evolved from "basic insulation" to a more diversified approach, including "lightweight, long-lasting stability, and temperature response." Traditional thermal insulation fabrics mostly rely on filling materials such as down, wool, and polyester fibers. While these materials can achieve a certain level of warmth, they have inherent drawbacks: natural materials such as down and wool are prone to absorbing moisture and clumping, resulting in a sharp drop in warmth in humid environments, and they are also prone to deformation and down leakage after washing; synthetic fibers such as polyester fibers rely on the air layer between fibers for warmth, requiring increased fabric thickness to achieve sufficient warmth, leading to bulky wear, poor breathability, and unsuitability for outdoor activities such as mountaineering and commuting, where "lightweight and flexible" are required.

[0003] To overcome the limitations of traditional fabrics, functional thermal insulation materials have gradually become a research hotspot, with silica aerogel considered an ideal insulation component due to its extremely low thermal conductivity. However, traditional silica aerogel suffers from a rigid and brittle skeleton—its microstructure is mainly composed of a dense cross-linked network formed by Si-O-Si covalent bonds, lacking flexible adjustment units. When combined with fabrics, it is prone to powdering and detachment after bending and friction, and its functional retention rate is often less than 80% after multiple washes, failing to meet the durability requirements for long-term fabric use. Furthermore, single aerogel fabrics can only provide passive insulation and cannot dynamically adjust heat according to changes in ambient temperature. In scenarios with large diurnal temperature differences or fluctuations in human body heat production, it is prone to "overcooling" or "overheating" problems.

[0004] To achieve temperature response functionality, the industry often combines phase change microcapsules (such as paraffin-based microcapsules) with aerogels. However, existing compounding technologies have two major bottlenecks: First, phase change microcapsules and aerogels are mostly physically mixed, and the interface between the two lacks chemical bonding. The microcapsules are prone to agglomeration and detachment after washing, resulting in a decrease in temperature response efficiency. Second, the wall material design of phase change microcapsules is unreasonable. The wall material lacks active functional groups and cannot form a stable bond with aerogel. In addition, paraffin itself has a low thermal conductivity. When there is a lack of efficient thermally conductive fillers, the phase change endothermic / exothermic response is slow and it is difficult to quickly adapt to temperature changes. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the existing technology and to propose a temperature-responsive aerogel composite thermal insulation fabric and its preparation method.

[0006] To achieve the above objectives, the present invention provides a temperature-responsive aerogel composite thermal insulation fabric, comprising a base fabric layer and a thermal insulation functional layer coated on the surface of the base fabric layer.

[0007] The thermal insulation layer comprises the following raw materials in parts by weight: modified silica aerogel: 30-40 parts, phase change microcapsules: 20-30 parts, waterborne polyurethane adhesive: 15-25 parts, binding catalyst: 0.5-1 parts, and deionized water: 120-160 parts.

[0008] The modified silica aerogel is prepared as follows:

[0009] (1) In a nitrogen-protected three-necked flask, anhydrous diethyl ether and magnesium shavings were added. Dibromoalkanes were added dropwise with stirring at room temperature to initiate the reaction. After the reaction was initiated, the addition was continued, and an ice-water bath was used to maintain the reaction temperature at 20-30℃. After the addition was completed, the reaction was carried out at room temperature for 30-60 min to obtain a bis(magnesium bromide)alkane solution. The solution was cooled to 0℃, and trimethoxychlorosilane was added. Then the reaction was allowed to return to room temperature for 8-12 h. The precipitate was removed by filtration, the solvent was removed by rotary evaporation, and then bis(trimethoxysilyl)alkanes were obtained by vacuum distillation. The chemical reaction equation is as follows:

[0010] The product was characterized by ¹H NMR. This step of the reaction synthesizes the target long-chain silane through a bi-Grignard reaction and nucleophilic substitution. Essentially, it utilizes the dihalogenation property of dibromoalkanes to form a bi-Grignard reagent with magnesium, followed by selective substitution with trimethoxychlorosilane to introduce long-chain alkyl and siloxane groups. Specifically, in an anhydrous diethyl ether system under nitrogen protection, magnesium shavings and dibromoalkanes first initiate the reaction: the C-Br bond at one end of the dibromoalkane is attacked by the metallic electrons of magnesium, and Mg inserts into the C-Br bond to generate a mono-Grignard intermediate. The ice-water bath temperature of 20-30℃ is used to avoid excessively rapid exothermic reaction that could damage the solvent. Boiling; after the addition is complete, react at room temperature for 30-60 minutes, allowing the C-Br bond at the other end of the intermediate to continue reacting with excess magnesium, eventually forming bis(magnesium bromide)alkane (a bis Grignard reagent, with -MgBr at both ends). Then, cool to 0°C and add trimethoxychlorosilane. At this point, the -MgBr of the bis Grignard reagent preferentially attacks the electronegative Si atom in the trimethoxychlorosilane, breaking the Si-Cl bond and undergoing a nucleophilic substitution reaction to generate bis(trimethoxysilyl)alkane and MgBrCl precipitate, yielding a bissiloxane containing long-chain alkyl groups, providing a "flexible framework" for subsequent aerogel flexible modification;

[0011] (2) Tetraethyl orthosilicate and bis(trimethoxysilyl)alkanes were added to ethanol, and dilute hydrochloric acid was added to adjust the pH to 4-5. The hydrolysis reaction was carried out for 1-2 hours. Then, ammonia was added to adjust the pH to 8-9. The temperature was raised to 50-60℃ and aged for 12-20 hours to obtain a wet gel. Then, 3-aminopropyltriethoxysilane was added, and the temperature was raised to 45-55℃. The reaction was shaken for 4-6 hours. After cooling to room temperature, methanol was used to replace the silica aerogel three times, each time for 8 hours. After drying with supercritical CO2, modified silica aerogel was obtained. The chemical reaction diagram is as follows:

[0012] ;

[0013] This process involves two steps: hydrolysis and condensation to construct a flexible framework, and grafting amino groups to introduce active sites. First, tetraethyl orthosilicate and bis(trimethoxysilyl)alkanes are hydrolyzed in ethanol under acidic conditions to form silanols. Then, ammonia is added to adjust the pH to 8-9, and silanol condensation is catalyzed under alkaline conditions. Aging allows the Si-OH groups of the silanol oligomers to undergo a condensation reaction (forming Si-O-Si bonds). Simultaneously, the long-chain alkyl groups of the bissiloxane are embedded into the silica framework. The molecular mobility of the long chains disperses stress, preventing excessive rigidity of the framework from causing embrittlement, ultimately forming a wet gel with a flexible structure. Next, 3-aminopropyltriethoxysilane (APTES) is added. The Si-OEt bonds of APTES hydrolyze to generate Si-OH, which condenses with the incompletely condensed Si-OH on the wet gel surface (forming Si-O-Si covalent bonds), anchoring APTES to the aerogel surface. Furthermore, the amino groups of APTES remain in a free state (unprotonated) under alkaline conditions, preserving them intact as subsequent active sites.

[0014] The preparation method of the phase change microcapsules is as follows:

[0015] Paraffin wax and nano-boron nitride were mixed, and deionized water and sodium dodecylbenzenesulfonate were added. The mixture was ultrasonically dispersed for 20-30 min to obtain a core material solution. Methacrylic acid, styrene, and benzoyl peroxide were added to dichloromethane and stirred for 10-20 min. Then, the mixture was added to the core material solution and stirred vigorously. The mixture was heated to 60-80℃ and reacted for 3-5 h. After cooling to room temperature, the mixture was spray-dried to obtain phase change microcapsules. This step involves constructing an oil-in-water (O / W) emulsion, which allows the wall material monomers to polymerize on the surface of the core material to form a coating structure. At the same time, the carboxyl groups are retained for bonding with the aerogel amino groups. During the process, benzoyl peroxide decomposes to generate free radicals, which initiate a free radical copolymerization reaction between methacrylic acid and styrene to form a carboxyl-containing polymer wall material on the surface of the paraffin droplets (the carboxyl groups of methacrylic acid are retained on the surface of the wall material), resulting in a phase change microcapsule consisting of a "paraffin core material + carboxyl-containing polymer wall material".

[0016] Preferably, the solid content of the waterborne polyurethane adhesive is 30-40%.

[0017] Preferably, the catalyst refers to 1-ethyl-(3-dimethylaminopropyl)carbodiimide.

[0018] Preferably, the molar ratio of magnesium shavings, dibromoalkanes and trimethoxychlorosilane in (1) is 1:0.4-0.5:0.4-0.5.

[0019] Preferably, in (1), the magnesium shavings and anhydrous ether are in a weight ratio of 1:15-25.

[0020] Preferably, the general structural formula of the dibromoalkane in (1) is: , where n = 6 - 10.

[0021] Preferably, in (2), the weight ratio of tetraethyl orthosilicate, bis(trimethoxysilyl)alkanes, ethanol and 3-aminopropyltriethoxysilane is 1:0.2-0.3:8-12:0.1-0.2; and the concentration of dilute hydrochloric acid is 1 mol / L.

[0022] Preferably, in the preparation method of the phase change microcapsules, paraffin, nano boron nitride, deionized water, sodium dodecylbenzenesulfonate, methacrylic acid, styrene, benzoyl peroxide and dichloromethane are in a weight ratio of 70-80:3-7:250-300:1-3:15-25:12-20:0.3-0.7:60-80.

[0023] Furthermore, the present invention also provides a method for preparing a temperature-responsive aerogel composite thermal insulation fabric, comprising the following steps:

[0024] S1. Modified silica aerogel and phase change microcapsules are added to deionized water and ultrasonically dispersed for 10-20 min. Then, a binding catalyst is added, and the mixture is heated to 35-45℃ and stirred for 2-3 h. Next, waterborne polyurethane adhesive is added, and stirring is continued for 20-30 min to obtain a composite thermal insulation slurry. In this step, the carboxyl groups of the phase change microcapsule wall material first undergo nucleophilic addition with the carbodiimide structure (-N=C=N-) of the binding catalyst to generate an O-acyl isourea intermediate with higher reactivity. The heating condition of 35-45℃ can enhance the catalytic activity of EDC and accelerate the formation of the intermediate. Subsequently, the amino groups on the surface of the modified silica aerogel (grafted with APTES) nucleophilically attack the carbonyl carbon of the intermediate, initiating a substitution reaction to form a stable amide bond (-CONH-), thus achieving chemical bonding between the two.

[0025] S2. The base fabric layer is subjected to corona treatment with a power of 300-500W for 20-30s. The composite thermal insulation slurry is then applied to the surface of the base fabric layer to obtain a composite thermal insulation layer. The thickness of the composite thermal insulation layer is controlled to be 0.2-0.4mm. The layer is then placed in an oven at 100-120℃ to dry and cure. After cooling to room temperature, a temperature-responsive aerogel composite thermal insulation fabric is obtained.

[0026] Preferably, the base fabric layer in S2 includes one of the following: polyester base fabric, nylon base fabric, polyester-cotton blended base fabric, polyester-spandex blended base fabric, nylon-polyester blended base fabric, PTFE membrane composite polyester base fabric, PU waterproof coated nylon base fabric, and polyester nonwoven base fabric.

[0027] More preferably, the base fabric layer in S2 refers to a polyester base fabric.

[0028] Preferably, the working mechanism of the temperature-responsive aerogel composite thermal insulation fabric of the present invention is as follows:

[0029] The modified silica aerogel has a structure consisting of a rigid Si-O-Si framework and long-chain alkyl flexible spacers. The synthesized bis(trimethoxysilyl)alkanes (containing C6-C) 10During hydrolysis and condensation, the Si-OCH3 bond of the long-chain alkyl group and the Si-OEt bond of tetraethyl orthosilicate hydrolyze together to form Si-OH, which then condenses under alkaline conditions to form Si-O-Si covalent bonds, constructing the porous framework of the aerogel. Simultaneously, the long-chain alkyl group in the bissiloxane is embedded in the gaps between the Si-O-Si framework, utilizing the molecular mobility of the long-chain alkyl group to disperse stress—when the fabric is subjected to external bending, the long-chain alkyl group can undergo conformational adjustment, preventing the Si-O-Si framework from breaking due to excessive rigidity, thus solving the embrittlement problem of traditional aerogels. Furthermore, the nanoscale pores formed by the Si-O-Si framework can confine the flow of air molecules, reducing convective heat transfer, while the hydrophobic properties of the long-chain alkyl group can inhibit water condensation within the pores. To prevent moisture from damaging the insulation, the two work together to give the aerogel low thermal conductivity, providing basic insulation for the fabric. The microscopic heat storage and temperature response function of the phase change microcapsules is achieved by the conformational change of the hydrocarbon groups in the paraffin core material and the stabilizing effect of the carboxyl groups in the polymer wall material: the paraffin core material is a long-chain alkane, and when the temperature reaches the phase change point, the hydrocarbon groups in its molecules will change from an ordered crystalline state to a disordered molten state, absorbing heat in the process; when the temperature is lower than the phase change point, the hydrocarbon groups will recrystallize in an ordered manner, releasing the stored heat and achieving a dynamic response to the ambient temperature. The wall material is formed by copolymerization of methacrylic acid and styrene, in which the carboxyl groups combine with the hydrocarbon groups of the paraffin core material through intermolecular forces during polymerization, enhancing the interfacial bonding between the wall material and the core material. The presence of carboxyl groups provides active sites for subsequent bonding with the aerogel, ensuring stable dispersion of the microcapsules in the fabric and preventing them from detaching during washing or friction. The stability of the fabric composite insulation layer depends on the covalent amide bond between the aerogel and the microcapsules. The modified aerogel surface retains free amino groups through grafting with 3-aminopropyltriethoxysilane (APTES). The methacrylic acid units of the phase change microcapsule wall material retain carboxyl groups. In step S1, 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) acts as a catalyst, first reacting with the carboxyl groups to generate a highly active O-acylisourea intermediate. Subsequently, this intermediate undergoes a nucleophilic substitution reaction with the amino groups to form stable amide bonds. This covalent bond effectively eliminates the interfacial gap between aerogel and microcapsules, avoiding the problems of "aerogel particle shedding and microcapsule aggregation" in traditional physical mixing, ensuring long-term synergy between thermal insulation and heat storage functions. The temperature-responsive insulation function of the fabric is the microscopic synergy of "aerogel thermal insulation + microcapsule heat storage": the Si-O-Si porous framework of the aerogel inhibits heat conduction and heat convection, blocking the transfer of low external temperatures to the fabric interior, while reducing the loss of internal heat to the outside; when the local temperature drops below the phase transition point due to heat dissipation from the human body, the hydrocarbon crystals of the microcapsule paraffin core material release heat to compensate for the heat loss; when the external temperature rises or the human body generates more heat, the paraffin hydrocarbons melt and absorb excess heat, preventing overheating inside the fabric.The amide bonds between the aerogel and the microcapsules, the Si-O-Si bonds in the aerogel skeleton, and the C-C covalent bonds in the microcapsule wall material (formed by copolymerization of styrene and methacrylic acid) together constitute a stable microstructure network, ensuring that the above-mentioned heat insulation and heat storage functions do not fail under usage scenarios such as fabric bending, washing, and friction, ultimately achieving the effect of "dynamic temperature control + long-lasting warmth".

[0030] The beneficial effects of this invention are:

[0031] 1. This invention effectively solves the problems of high brittleness and easy pulverization of traditional aerogels by modifying silica aerogels with long-chain alkyl groups. During the aerogel preparation process, when bis(trimethoxysilyl)alkane (containing C6-C10 long-chain alkyl groups) co-condenses with tetraethyl orthosilicate, the long-chain alkyl groups are uniformly embedded in the gaps between the Si-O-Si rigid framework, and the stress under external force is dispersed by the rotational motion of the long-chain molecules. This "rigid framework + flexible long chain" microstructure can avoid the framework breakage caused by local stress concentration when the aerogel is bent and rubbed, greatly reducing the risk of pulverization. Even after repeated bending and washing, the fabric can still maintain its structural integrity, meeting the durability requirements for long-term wear and use, and is especially suitable for outdoor, commuting and other scenarios requiring frequent activity.

[0032] 2. This invention achieves long-term stability of the fabric's thermal insulation performance by optimizing the aerogel structure and the integration of the functional layer. The modified silica aerogel retains the nanoscale pores formed by the Si-O-Si framework. These pores are smaller than the free path of air molecules, effectively binding the movement of air molecules, suppressing convective heat transfer, and giving the fabric excellent basic thermal insulation capabilities. Simultaneously, the hydrophobic properties of the long-chain alkyl groups reduce moisture condensation within the pores, preventing moisture from damaging the thermal insulation performance. More importantly, the amino groups on the aerogel surface and the carboxyl groups of the phase change microcapsule wall material form stable amide bonds under the action of a catalyst, firmly anchoring the functional layer and preventing it from detaching due to washing or friction. This ensures the fabric maintains low thermal conductivity over a long period, consistently maintaining a high-efficiency thermal insulation effect.

[0033] 3. This invention, through the optimized design of phase change microcapsules, endows fabrics with efficient temperature response and dynamic temperature control capabilities. The phase change microcapsules, using paraffin as the core material, can achieve heat absorption and storage, as well as heat release and release, through hydrocarbon conformational changes within a specific temperature range, dynamically balancing the internal temperature of the fabric. Simultaneously, the nano-boron nitride added to the microcapsules constructs a highly efficient thermally conductive network, significantly improving the heat transfer efficiency of paraffin, accelerating the heat absorption and release rates of the phase change process, and avoiding temperature regulation lag. This design allows the fabric to quickly absorb excess heat when the ambient temperature rises, preventing overheating; and to promptly release stored heat when the temperature drops, replenishing heat loss, adapting to scenarios with diurnal temperature fluctuations or changes in human body heat production, thus improving wearing comfort.

[0034] 4. This invention significantly enhances the bonding strength between the thermal insulation layer and the base fabric through a synergistic effect of "chemical bonding + physical adhesion." On one hand, the amino groups of the modified aerogel form amide bonds with the carboxyl groups of the phase change microcapsules, achieving molecular-level connections within the functional layer. On the other hand, the water-based polyurethane adhesive, acting as a binder, allows its hydroxyl groups to form hydrogen bonds with the hydroxyl groups of the base fabric fibers, further strengthening the interfacial bonding between the functional layer and the base fabric through physical encapsulation. This dual-bonding system effectively resists external forces such as stretching and peeling, preventing the thermal insulation layer from separating from the base fabric during use, ensuring the integrity of the fabric structure, extending its service life, and providing good adaptability for subsequent fabric processing (such as cutting and sewing). Attached Figure Description

[0035] Figure 1 The H NMR spectrum of 1,6-bis(trimethoxysilyl)hexane prepared in Example 1 of this invention;

[0036] Figure 2 The 1H NMR spectrum of 1,8-bis(trimethoxysilyl)octane prepared in Example 2 of this invention;

[0037] Figure 3 The 1,10-bis(trimethoxysilyl)decane prepared in Example 3 of this invention has an 1H NMR spectrum. Detailed Implementation

[0038] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.

[0039] Preparation Example 1: The specific preparation method of modified silica aerogel includes the following steps:

[0040] (1) In a nitrogen-protected three-necked flask, 150 g of anhydrous diethyl ether and 10 g of magnesium shavings were added. 40.15 g of 1,6-dibromohexane was added dropwise with stirring at room temperature to initiate the reaction. After initiation, the addition continued, and an ice-water bath was used to maintain the reaction temperature at 20 °C. After the addition was complete, the reaction was carried out at room temperature for 30 min to obtain a 1,6-bis(magnesium bromide)hexane solution. The solution was cooled to 0 °C, and 17.88 g of trimethoxychlorosilane was added. The reaction was then allowed to return to room temperature and continue for 8 h. The precipitate was removed by filtration, the solvent was removed by rotary evaporation, and then 1,6-bis(trimethoxysilyl)hexane was obtained by vacuum distillation. The structure of 1,6-bis(trimethoxysilyl)hexane was characterized by ¹H NMR, and the spectrum is attached. Figure 1 As shown;

[0041] (2) Add 100g of tetraethyl orthosilicate and 20g of 1,6-bis(trimethoxysilyl)hexane to 800g of ethanol, add 1mol / L of dilute hydrochloric acid to adjust the pH to 4, hydrolyze for 1h, then add ammonia to adjust the pH to 8, heat to 50℃, age for 12h to obtain wet gel, then add 10g of 3-aminopropyltriethoxysilane, heat to 45℃, shake for 4h, cool to room temperature, replace with methanol 3 times, 8h each time, and dry with supercritical CO2 to obtain modified silica aerogel.

[0042] Preparation Example 2: The specific preparation method of modified silica aerogel includes the following steps:

[0043] (1) In a nitrogen-protected three-necked flask, 200 g of anhydrous diethyl ether and 10 g of magnesium shavings were added. 50.36 g of 1,8-dibromooctane was added dropwise with stirring at room temperature to initiate the reaction. After the reaction was initiated, the addition continued, and an ice-water bath was used to maintain the reaction temperature at 25 °C. After the addition was complete, the reaction was carried out at room temperature for 45 min to obtain a 1,8-bis(magnesium bromide)octane solution. The solution was cooled to 0 °C, and 20.11 g of trimethoxychlorosilane was added. The reaction was then allowed to return to room temperature and carried out for 8 h. The precipitate was removed by filtration, the solvent was removed by rotary evaporation, and then 1,8-bis(trimethoxysilyl)octane was obtained by vacuum distillation. The structure of 1,8-bis(trimethoxysilyl)octane was characterized by ¹H NMR, and the spectrum is attached. Figure 2 As shown;

[0044] (2) Add 100g of tetraethyl orthosilicate and 25g of 1,8-bis(trimethoxysilyl)octane to 1kg of ethanol, add 1mol / L of dilute hydrochloric acid to adjust the pH to 4.5, hydrolyze for 1.5h, then add ammonia to adjust the pH to 8.5, heat to 55℃, age for 16h to obtain wet gel, then add 15g of 3-aminopropyltriethoxysilane, heat to 50℃, shake for 5h, cool to room temperature, replace with methanol 3 times, 8h each time, and dry with supercritical CO2 to obtain modified silica aerogel.

[0045] Preparation Example 3: The specific preparation method of modified silica aerogel includes the following steps:

[0046] (1) In a nitrogen-protected three-necked flask, 250 g of anhydrous diethyl ether and 10 g of magnesium shavings were added. 61.73 g of 1,10-dibromodecane was added dropwise with stirring at room temperature to initiate the reaction. After the reaction was initiated, the addition continued, and an ice-water bath was used to maintain the reaction temperature at 30 °C. After the addition was complete, the reaction was carried out at room temperature for 60 min to obtain a 1,10-bis(magnesium bromide)decane solution. The solution was cooled to 0 °C, and 22.35 g of trimethoxychlorosilane was added. The reaction was then allowed to return to room temperature and carried out for 8 h. The precipitate was removed by filtration, the solvent was removed by rotary evaporation, and then 1,10-bis(trimethoxysilyl)decane was obtained by vacuum distillation. The structure of 1,10-bis(trimethoxysilyl)decane was characterized by ¹H NMR, and the spectrum is attached. Figure 3 As shown;

[0047] (2) Add 100g of tetraethyl orthosilicate and 30g of 1,10-bis(trimethoxysilyl)decane to 1.2kg of ethanol, add 1mol / L of dilute hydrochloric acid to adjust the pH to 5, hydrolyze for 2h, then add ammonia to adjust the pH to 9, heat to 60℃, age for 20h to obtain wet gel, then add 20g of 3-aminopropyltriethoxysilane, heat to 55℃, shake for 6h, cool to room temperature, replace with methanol 3 times, 8h each time, and dry with supercritical CO2 to obtain modified silica aerogel.

[0048] Preparation Example 4: The specific preparation method of phase change microcapsules includes the following steps:

[0049] 70g of paraffin and 3g of nano-boron nitride were mixed, and 250g of deionized water and 1g of sodium dodecylbenzenesulfonate were added. The mixture was ultrasonically dispersed for 20min to obtain a core material solution. 15g of methacrylic acid, 12g of styrene and 0.3g of benzoyl peroxide were added to 60g of dichloromethane and stirred for 10min. The mixture was then added to the core material solution. Under vigorous stirring, the mixture was heated to 60℃ and reacted for 3h. After cooling to room temperature, the mixture was spray-dried to obtain phase change microcapsules.

[0050] Preparation Example 5: The specific preparation method of phase change microcapsules includes the following steps:

[0051] 75g of paraffin and 5g of nano-boron nitride were mixed, and 275g of deionized water and 2g of sodium dodecylbenzenesulfonate were added. The mixture was ultrasonically dispersed for 25min to obtain a core material solution. 20g of methacrylic acid, 16g of styrene and 0.5g of benzoyl peroxide were added to 70g of dichloromethane and stirred for 15min. Then the mixture was added to the core material solution. The mixture was stirred vigorously and heated to 70℃ for 4h. After cooling to room temperature, the mixture was spray-dried to obtain phase change microcapsules.

[0052] Preparation Example 6: A specific method for preparing phase change microcapsules, including the following steps:

[0053] 80g of paraffin and 7g of nano-boron nitride were mixed, and 300g of deionized water and 3g of sodium dodecylbenzenesulfonate were added. The mixture was ultrasonically dispersed for 30min to obtain a core material solution. 25g of methacrylic acid, 20g of styrene and 0.7g of benzoyl peroxide were added to 80g of dichloromethane and stirred for 20min. Then the mixture was added to the core material solution. The mixture was stirred vigorously and heated to 80℃ for 5h. After cooling to room temperature, the mixture was spray-dried to obtain phase change microcapsules.

[0054] Comparative Preparation Example 1: The difference between Comparative Preparation Example 1 and Preparation Example 2 is that 1,8-dibromooctane is replaced with 1,2-dibromoethane.

[0055] Comparative Preparation Example 2: The difference between Comparative Preparation Example 2 and Preparation Example 2 is that 1,8-dibromooctane is replaced with 1,4-dibromobutane.

[0056] Comparative Preparation Example 3: The difference between Comparative Preparation Example 3 and Preparation Example 2 is that 1,8-dibromooctane is replaced with 1,12-dibromododecane.

[0057] Comparative Preparation Example 4: The difference between Comparative Preparation Example 4 and Preparation Example 2 is that 1,8-dibromooctane is replaced with 1,14-dibromotetradecane.

[0058] Comparative Preparation Example 5: The difference between Comparative Preparation Example 5 and Preparation Example 2 is that 3-aminopropyltriethoxysilane is not added.

[0059] Comparative Preparation Example 6: The difference between Comparative Preparation Example 6 and Preparation Example 5 is that methacrylic acid is replaced with methyl methacrylate.

[0060] Comparative Preparation Example 7: The difference between Comparative Preparation Example 7 and Preparation Example 5 is that no nano boron nitride is added.

[0061] Example 1: A specific preparation method for a temperature-responsive aerogel composite thermal insulation fabric, comprising the following steps:

[0062] S1. Add 300g of the modified silica aerogel prepared according to Preparation Example 1 and 200g of the phase change microcapsules prepared according to Preparation Example 4 to 1.2kg of deionized water, and ultrasonically disperse for 10min. Then add 5g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, heat to 35℃ and stir for 2h. Then add 150g of waterborne polyurethane adhesive with a solid content of 30% and continue stirring for 20-30min to obtain the composite thermal insulation slurry.

[0063] S2. The polyester base fabric is subjected to corona treatment with a power of 300W for 20s. The composite thermal insulation paste is then applied to the surface of the base fabric layer to obtain a composite thermal insulation layer. The thickness of the composite thermal insulation layer is controlled to be 0.2mm. Then, it is placed in a 100℃ oven to dry and cure. After cooling to room temperature, a temperature-responsive aerogel composite thermal insulation fabric is obtained.

[0064] Example 2: A specific preparation method for a temperature-responsive aerogel composite thermal insulation fabric, comprising the following steps:

[0065] S1. 350g of the modified silica aerogel prepared according to Preparation Example 2 and 250g of the phase change microcapsules prepared according to Preparation Example 5 were added to 1.4kg of deionized water and ultrasonically dispersed for 15min. Then, 7.5g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide was added, the temperature was raised to 40℃ and stirred for 2.5h. Then, 200g of waterborne polyurethane adhesive with a solid content of 35% was added and stirred for another 25min to obtain the composite thermal insulation slurry.

[0066] S2. The polyester base fabric is subjected to corona treatment with a power of 400W for 25s. The composite thermal insulation paste is then applied to the surface of the base fabric layer to obtain a composite thermal insulation layer. The thickness of the composite thermal insulation layer is controlled to be 0.3mm. Then, it is placed in an oven at 110℃ to dry and cure. After cooling to room temperature, a temperature-responsive aerogel composite thermal insulation fabric is obtained.

[0067] Example 3: A specific preparation method for a temperature-responsive aerogel composite thermal insulation fabric, comprising the following steps:

[0068] S1. Add 400g of the modified silica aerogel prepared according to Preparation Example 3 and 300g of the phase change microcapsules prepared according to Preparation Example 6 to 1.6kg of deionized water, and ultrasonically disperse for 20min. Then add 10g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, heat to 45℃ and stir for 3h. Then add 250g of waterborne polyurethane adhesive with a solid content of 40% and continue stirring for 30min to obtain the composite thermal insulation slurry.

[0069] S2. The polyester base fabric is subjected to corona treatment with a power of 500W for 30s. The composite thermal insulation paste is then applied to the surface of the base fabric layer to obtain a composite thermal insulation layer. The thickness of the composite thermal insulation layer is controlled to be 0.4mm. Then, it is placed in a 120℃ oven to dry and cure. After cooling to room temperature, a temperature-responsive aerogel composite thermal insulation fabric is obtained.

[0070] Those skilled in the art will know that by replacing the aforementioned polyester base fabric with nylon base fabric, polyester-cotton blended base fabric, or other base materials, the composite fabric of the present invention can be obtained through the same process, with no substantial difference in performance.

[0071] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that the modified silica aerogel prepared according to Preparation Example 2 is replaced with the modified silica aerogel prepared according to Comparative Preparation Example 1.

[0072] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the modified silica aerogel prepared according to Preparation Example 2 is replaced with the modified silica aerogel prepared according to Comparative Preparation Example 2.

[0073] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that the modified silica aerogel prepared according to Preparation Example 2 is replaced with the modified silica aerogel prepared according to Comparative Preparation Example 3.

[0074] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that the modified silica aerogel prepared according to Preparation Example 2 is replaced with the modified silica aerogel prepared according to Comparative Preparation Example 4.

[0075] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that the modified silica aerogel prepared according to Preparation Example 2 is replaced with the modified silica aerogel prepared according to Comparative Preparation Example 5.

[0076] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that the modified silica aerogel prepared according to Preparation Example 2 is replaced with unmodified silica aerogel.

[0077] Comparative Example 7: The difference between Comparative Example 7 and Example 2 is that the phase change microcapsules prepared according to Preparation Example 5 are replaced with the phase change microcapsules prepared according to Comparative Preparation Example 6.

[0078] Comparative Example 8: The difference between Comparative Example 8 and Example 2 is that the phase change microcapsules prepared according to Preparation Example 5 are replaced with the phase change microcapsules prepared according to Comparative Preparation Example 7.

[0079] Performance testing:

[0080] 1. Anti-embrittlement performance test: Fabric samples from Examples 1-3 and Comparative Examples 1-8 were selected and cut into rectangular specimens of 100mm×50mm. Referring to GB / T 3923.1-2013 standard for testing tensile properties of textiles, the bending module of the YG(B)026D electronic fabric strength tester was used. The bending angle was set to ±90° and the bending rate to 30 times / min. After 100 consecutive bending cycles, the specimens were weighed on an electronic balance with an accuracy of 0.1mg (recorded as m1). Then, the aerogel powder that fell off the surface was gently brushed off with a soft brush and weighed again (recorded as m2). The powdering rate was calculated as (m1-m2) / m1×100%. At the same time, it was observed whether cracks appeared on the fabric surface. The experimental results are shown in Table 1.

[0081] 2. Steady-state thermal conductivity test: Fabric samples of 200mm×200mm were taken from Examples 1-3 and Comparative Examples 1-8 and equilibrated for 24 hours in an environment with a temperature of 25℃ and a relative humidity of 65%. Referring to GB / T 10294-2008 Determination of Steady-state Thermal Resistance and Related Properties of Thermal Insulation Materials - Protective Hot Plate Method, a DRL-III thermal conductivity tester was used. The cold plate temperature was set to 10℃ and the hot plate temperature to 35℃. A pressure of 10kPa was applied to ensure the sample was in contact with the plate. After the system reached steady state (temperature difference fluctuation ≤0.1℃), the thermal conductivity value was recorded. The experimental results are shown in Table 1.

[0082] 3. Washing resistance test: Fabric samples from Examples 1-3 and Comparative Examples 1-8 were cut to 200mm×200mm. Following the washing and drying procedures in GB / T 8629-2017 Textiles, a SW-12A type wash fastness tester was used. The washes were performed 50 times (each wash included 15 minutes of washing, two 5-minute rinses, and a 3-minute dehydration) at 40℃ water temperature, 1g / L standard detergent, and a liquor ratio of 1:50. After washing, the fabrics were dried in a 50℃ oven to constant weight. The thermal conductivity and functional layer shedding rate were then tested. The weight change of the fabric before and after washing was calculated using the weighing method: shedding rate = (weight before washing - weight after washing) / weight before washing × 100%. The experimental results are shown in Table 1.

[0083] 4. Phase change enthalpy and temperature response rate test: Take 5g of each fabric sample from Examples 1-3 and Comparative Examples 1-8, and refer to GB / T 29866-2013 Test Method for Phase Change Temperature Regulation Performance of Textiles. Use a DSC-60 differential scanning calorimeter, set the heating rate to 5℃ / min, and the test temperature range to 0-50℃ (covering the paraffin phase change range of 28-32℃). Record the DSC curve and calculate the phase change enthalpy (endothermic and exothermic enthalpies). At the same time, take 100mm×100mm of each fabric sample and attach it to a 37℃ constant temperature heating plate. Use a T-type thermocouple to record the surface temperature change of the fabric in real time. Statistically, the time from 25℃ to 32℃ (endothermic endpoint) and the time from 32℃ to 25℃ (exothermic endpoint) are recorded. The experimental results are shown in Table 1.

[0084] 5. Peel strength test between the thermal insulation layer and the base fabric: Fabric samples from Examples 1-3 and Comparative Examples 1-8 were selected and cut into 150mm×25mm specimens. Referring to GB / T 2791-1995 Adhesives T Peel Strength Test Method, an XLW(L) type intelligent electronic tensile testing machine was used to peel the base fabric layer and the thermal insulation layer of the fabric apart by 50mm from one end. The samples were clamped on the upper and lower clamps of the testing machine, and the tensile rate was set to 100mm / min. The machine was started until the functional layer and the base fabric were completely peeled apart. The maximum force value during the peeling process was recorded, and the peel strength was calculated as: maximum force value / specimen width, in N / cm. The experimental results are shown in Table 1.

[0085] Table 1 Performance Test Results

[0086] Performance Analysis:

[0087] As can be seen from the experimental data in Table 1, the thermal insulation fabric prepared by the present invention in the examples, through the synergistic design of long-chain alkyl modified aerogel, carboxyl-amino chemical bonding, and nano-boron nitride thermal conductivity enhancement, is significantly better than the comparative examples in terms of core performance such as anti-embrittlement, thermal insulation, water washing stability, phase change response efficiency, and interlayer bonding strength. Among them, Example 2 has the best overall performance.

[0088] From the perspective of anti-embrittlement performance, the superior performance of Example 2 stems from the "flexibility-strength balance regulation" of the aerogel skeleton by the C8 long-chain alkyl group: the length of the C8 long chain matches the spacing of the Si-O-Si crosslinking points, allowing it to be evenly interspersed in the gaps of the skeleton. This disperses bending stress through the rotational movement of the long-chain molecules without interfering with the crosslinking density of the Si-O-Si bonds, avoiding skeleton fracture caused by local stress concentration. Therefore, the pulverization rate is low and there are no cracks. In comparison with the comparative examples: Comparative examples 1-2 (C2 / C4 short chains) cannot effectively disperse stress due to their short carbon chains, resulting in excessively rigid skeletons. When bent, the Si-O-Si bonds are easily broken directly. Comparative examples 3-4 have excessively long carbon chains, which easily cause chain entanglement, resulting in uneven distribution of crosslinking points and sparse crosslinking in some areas, leading to preferential fracture under stress. Comparative example 6 has no long-chain buffer, and the skeleton relies entirely on rigid Si-O-Si bonds for support. When bent, it becomes embrittled directly, resulting in the most severe pulverization.

[0089] Example 2 exhibits low thermal conductivity and stability after washing, possibly due to the dual effect of "porous structure retention + chemical bonding fixation": the diameter of the C8 long chain is much smaller than the nanopores of the aerogel, preventing pore blockage; the high porosity effectively traps air and suppresses convective heat transfer; simultaneously, the amino groups grafted onto the aerogel surface by APTES and the carboxyl groups of the microcapsules form stable amide bonds under EDC catalysis, anchoring the functional layer to the base fabric, with no significant detachment during washing and minimal change in thermal conductivity; Comparison with comparative examples: Comparative Examples 1-2 (C2 / Due to excessive cross-linking, the porosity of the C4 short chain aerogel decreased, resulting in enhanced convective heat transfer and a higher initial thermal conductivity. Comparative Examples 3-4 (C12 / C14 long chains) also experienced a decrease in porosity due to partial blockage of pores by the long chains, resulting in a slightly higher thermal conductivity. Comparative Examples 5 (without APTES) and 7 (without carboxyl microcapsules) lacked amide bonds, and the functional layers were bound only by physical adsorption, leading to significant detachment after washing and a substantial increase in thermal conductivity. Comparative Example 6 (unmodified aerogel) had the highest initial thermal conductivity due to the tendency of pores to collapse, and this deteriorated further after washing.

[0090] Example 2 exhibits stable phase change enthalpy and rapid response, which may be because during microcapsule polymerization, the carboxyl groups of methacrylic acid copolymerize with the wall material monomers to form a dense capsule wall, resulting in high paraffin coating efficiency and a phase change enthalpy close to the theoretical value. Simultaneously, nano-boron nitride is uniformly dispersed in the paraffin, providing a high thermal conductivity and forming a thermally conductive network, accelerating heat transfer within the paraffin and resulting in short heat absorption and release times. In contrast, Comparative Example 8 (without boron nitride) lacks a thermally conductive network, and heat is transferred solely by the paraffin itself, leading to a significantly prolonged response time.

[0091] The high peel strength of Example 2 is due to the formation of amide bonds between the amino groups on the surface of the modified silica aerogel and the carboxyl groups of the microcapsules through EDC catalysis, achieving molecular-level chemical bonding. Simultaneously, the hydroxyl groups of the waterborne polyurethane adhesive form hydrogen bonds with the hydroxyl groups of the base fabric fibers, supplemented by van der Waals forces, constructing a dual "chemical + physical" bonding system with strong interlayer adhesion. In comparison, Comparative Example 5, lacking amino groups in its aerogel, cannot form amide bonds and relies solely on the physical bonding of the waterborne polyurethane adhesive, resulting in a significant decrease in peel strength. Comparative Example 7, lacking carboxyl groups in its microcapsules, also lacks amide bonds, leading to a significant reduction in peel strength. Comparative Example 6, lacking amino groups on its surface and prone to embrittlement, has a weak physical bond with the base fabric, resulting in the lowest peel strength.

[0092] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A temperature-responsive aerogel composite thermal insulation fabric, characterized in that, It includes a base fabric layer and a thermal insulation layer coated on the surface of the base fabric layer; The thermal insulation layer comprises the following raw materials in parts by weight: modified silica aerogel: 30-40 parts, phase change microcapsules: 20-30 parts, waterborne polyurethane adhesive: 15-25 parts, binding catalyst: 0.5-1 parts, and deionized water: 120-160 parts. The solid content of the waterborne polyurethane adhesive is 30-40%; The catalyst in question is 1-ethyl-(3-dimethylaminopropyl)carbodiimide.

2. The temperature-responsive aerogel composite thermal insulation fabric according to claim 1, characterized in that, The modified silica aerogel is prepared as follows: (1) In a nitrogen-protected three-necked flask, add anhydrous diethyl ether and magnesium shavings, and add dibromoalkanes dropwise with stirring at room temperature to initiate the reaction. Continue to add the dibromoalkanes dropwise while using an ice-water bath to maintain the reaction temperature at 20-30℃. After the addition is complete, react at room temperature for 30-60 min to obtain a bis(magnesium bromide)alkane solution. Cool to 0℃, add trimethoxychlorosilane, and then restore to room temperature. React for 8-12 h, filter to remove the precipitate, remove the solvent by rotary evaporation, and then obtain bis(trimethoxysilyl)alkanes by vacuum distillation. (2) Tetraethyl orthosilicate and bis(trimethoxysilyl)alkanes were added to ethanol, dilute hydrochloric acid was added, the pH was adjusted to 4-5, and the hydrolysis reaction was carried out for 1-2 hours. Then ammonia was added to adjust the pH to 8-9, the temperature was raised to 50-60℃, and the mixture was aged for 12-20 hours to obtain a wet gel. Then 3-aminopropyltriethoxysilane was added, the temperature was raised to 45-55℃, and the reaction was shaken for 4-6 hours. After cooling to room temperature, the mixture was replaced with methanol 3 times, each time for 8 hours. After drying with supercritical CO2, the modified silica aerogel was obtained.

3. The temperature-responsive aerogel composite thermal insulation fabric according to claim 2, characterized in that, In (1), the molar ratio of magnesium shavings, dibromoalkanes and trimethoxychlorosilane is 1:0.4-0.5:0.4-0.

5.

4. The temperature-responsive aerogel composite thermal insulation fabric according to claim 2, characterized in that, In (1), the magnesium shavings and anhydrous ether are in a weight ratio of 1:15-25.

5. The temperature-responsive aerogel composite thermal insulation fabric according to claim 2, characterized in that, The general structural formula of the dibromoalkane in (1) is: , where n = 6 - 10.

6. The temperature-responsive aerogel composite thermal insulation fabric according to claim 2, characterized in that, In (2), tetraethyl orthosilicate, bis(trimethoxysilyl)alkanes, ethanol and 3-aminopropyltriethoxysilane are in a weight ratio of 1:0.2-0.3:8-12:0.1-0.2; the concentration of dilute hydrochloric acid is 1 mol / L.

7. The temperature-responsive aerogel composite thermal insulation fabric according to claim 1, characterized in that, The preparation method of the phase change microcapsules is as follows: Paraffin wax and nano-boron nitride were mixed, and deionized water and sodium dodecylbenzenesulfonate were added. The mixture was ultrasonically dispersed for 20-30 minutes to obtain a core material solution. Methacrylic acid, styrene, and benzoyl peroxide were added to dichloromethane and stirred for 10-20 minutes. Then, the mixture was added to the core material solution. The mixture was stirred vigorously and heated to 60-80℃ for 3-5 hours. After cooling to room temperature, the mixture was spray-dried to obtain phase change microcapsules.

8. The temperature-responsive aerogel composite thermal insulation fabric according to claim 7, characterized in that, In the preparation method of the phase change microcapsules, paraffin, nano boron nitride, deionized water, sodium dodecylbenzenesulfonate, methacrylic acid, styrene, benzoyl peroxide and dichloromethane are in a weight ratio of 70-80:3-7:250-300:1-3:15-25:12-20:0.3-0.7:60-80.

9. The method for preparing the temperature-responsive aerogel composite thermal insulation fabric according to any one of claims 1-8, characterized in that, Includes the following steps: S1. Add modified silica aerogel and phase change microcapsules to deionized water, ultrasonically disperse for 10-20 min, add a binding catalyst, heat to 35-45℃ and stir for 2-3 h, then add waterborne polyurethane adhesive and continue stirring for 20-30 min to obtain composite thermal insulation slurry. S2. The base fabric layer is subjected to corona treatment with a power of 300-500W for 20-30s. The composite thermal insulation slurry is then applied to the surface of the base fabric layer to obtain a composite thermal insulation layer. The thickness of the composite thermal insulation layer is controlled to be 0.2-0.4mm. The layer is then placed in an oven at 100-120℃ to dry and cure. After cooling to room temperature, a temperature-responsive aerogel composite thermal insulation fabric is obtained.

10. The method for preparing the temperature-responsive aerogel composite thermal insulation fabric according to claim 9, characterized in that, The base fabric layer in S2 includes one of the following: polyester base fabric, nylon base fabric, polyester-cotton blended base fabric, polyester-spandex blended base fabric, nylon-polyester blended base fabric, PTFE membrane composite polyester base fabric, PU waterproof coated nylon base fabric, and polyester nonwoven base fabric.